Fabricating lightweight ceramics by spraying clay on knitted structures. (December 2022) - Gosch, Lukas; Jauk, Julian; Vašatko, Hana; Šamec, Elizabeta; Raffaelli, Matteo; Rutzinger, Stefan; Stavric, Milena
This research was carried out to develop a novel composite material consisting of a thread reinforcement and a clay matrix, as well as to develop a method of shaping this material into hollow spatial structures. Ceramic elements in the building industry are currently created by applying extruding, pressing and casting methods. The approach of spraying clay onto predefined knitted meshes increases the usability of digitally fabricated lightweight ceramic elements, while eliminating the need for scaffolding. In this approach, multiple layers of a fluid clay mass are sprayed onto the tensioned mesh using an industrial, six-axis robotic arm. This allows the precise application of the material and results in varying material thicknesses. Due to the complementary qualities of clay which absorbs compressive forces and threads which absorb tensile forces, lightweight structures can be created. The research involved experimenting with clay mixtures, several thread types, knitting methods and spraying techniques, as well as fabricating a 1:1 lightweight module as an architectural prototype.